The essence of the use of distributed ledger technology in the cryptocurrency market - U. M. Kaplanov (Путеводитель предпринимателя)
This article discusses the role of using distributed ledger technology in the cryptocurrency market. The concepts of «cryptocurrency» and «distributed registries» are analyzed. The mechanism of the operation of distributed registries on cryptocurrency markets is considered.